ANALISIS EKONOMI PRODUKSI KEDELAI HITAM DI KECAMATAN PLAYEN KABUPATEN GUNUNGKIDUL (BLACK SOYBEAN PRODUCTION ECONOMIC ANALYSIS IN PLAYEN SUB-DISTRIC, GUNUNG KIDUL) - Apsari, Sofia Rieni; R. Hermawan (Jurnal Ilmu-Ilmu Pertanian, 2009)
The effort to improve soybean farm business is related to the increase and the decrease of production due to changes in the usage of production factors. This research was conducted to study why soybean farm business is becoming less popular among farmers, from the economics of production point of view. The research was performed in Playen, Gunung Kidul District, to determine the efficiency of production factors usage, in terms to price. Tb retrieve sample at the sub-District level, villages were selected through Purposive Sampling Method, while 30 samples of farmer were selected randomly. For data analysis, the research used the Efficiency test of price, which is the comparison of MPV and marginal input cost or input price. The result was as follows: seed usage of t count 320.401 > t table 2.432; urea usage of count 69.291, t table 2.432; TSP fertilizer usage of t count 1140.281 > t table 2.432; KCL fertilizer usage of t count 666.949 > t table 2.432; Manure usage of t count 214.473 > t table 2.432; Pesticide usage of t count 1072.317> ttable2.432; Man power usage of t count 15.543> t table 2.43I. As the result show t count > t table 2.432 for all point, meaning the conclusion of this study is the usage of seed, urea, TSP, KCl, manure, pesticide and manpower were still below efficient.